2022
DOI: 10.1002/mabi.202200389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Degree of Deacetylation of Chitosan/Chitin on Human Neural Stem Cell Culture

Abstract: Stem cell therapy and research for neural diseases depends on reliable reproduction of neural stem cells. Chitosan-based materials have been proposed as a substrate for culturing human neural stem cells (hNSCs) in the pursuit of clinically compatible culture conditions that are chemically defined and compliant with good manufacturing practices. The physical and biochemical properties of chitosan and chitin are strongly regulated by the degree of deacetylation (DD). However, the effect of DD on hNSC behavior ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…The localized compression, tension, and nano- or microscale features of the substrate play a crucial role in regulating cell fate through cell transmembrane receptors, ultimately influencing cytoskeleton and cell morphology. In our previous study, we investigated the impact of different degrees of deacetylation on the mechanical properties of chitosan films [ 67 ]. We found that a higher degree of deacetylation led to a decrease in the elastic modulus of the films.…”
Section: Resultsmentioning
confidence: 99%
“…The localized compression, tension, and nano- or microscale features of the substrate play a crucial role in regulating cell fate through cell transmembrane receptors, ultimately influencing cytoskeleton and cell morphology. In our previous study, we investigated the impact of different degrees of deacetylation on the mechanical properties of chitosan films [ 67 ]. We found that a higher degree of deacetylation led to a decrease in the elastic modulus of the films.…”
Section: Resultsmentioning
confidence: 99%
“…In our earlier investigations, we have demonstrated that chitosan films with a higher degree of deacetylation (DD) exhibit the capacity to enhance human neural stem cell proliferation and sustain pluripotency. 37 In this study, 3D chitosan scaffolds were made out of medical grade chitosan (DD = 98.38%) using a freeze-drying technique to achieve a highly porous architecture. The architecture of these scaffolds was first examined in both their dry and hydrated states through scanning electron microscopy (SEM) and optical microscopy.…”
Section: Chitosan Scaffold Fabrication and Characterizationmentioning
confidence: 99%